Proceedings of the 3rd Workshop on Programming Languages and Operating Systems: Linguistic Support for Modern Operating Systems 2006
DOI: 10.1145/1215995.1216002
|View full text |Cite
|
Sign up to set email alerts
|

Type inference for unboxed types and first class mutability

Abstract: Systems programs rely on fine-grain control of data representation and use of state to achieve performance, conformance to hardware specification, and temporal predictability. The robustness and checkability of these programs could be greatly improved if modern type systems and programming language ideas, such as polymorphism and type inference, could be applied to these programs.BitC is a higher-order programming language in the tradition of ML and Haskell, extended to incorporate both state and the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…One of the central features of this approach was to create a new programming language for kernel implementation firstone that is safe, clean, and suitable for verification and low-level implementation at the same time. The idea was not necessarily to invent new language features, but rather to pick and choose from existing research and combine the necessary features into a targeted language for implementing verified OS kernels (Sridhar & Shapiro 2006;Shapiro 2006). This is a farreaching and long-term effort, but one with great appeal: The main kernel languages assembler, C, and C++ are old, with many unsafe features and were not built to ease program verification.…”
Section: Eros/coyotosmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the central features of this approach was to create a new programming language for kernel implementation firstone that is safe, clean, and suitable for verification and low-level implementation at the same time. The idea was not necessarily to invent new language features, but rather to pick and choose from existing research and combine the necessary features into a targeted language for implementing verified OS kernels (Sridhar & Shapiro 2006;Shapiro 2006). This is a farreaching and long-term effort, but one with great appeal: The main kernel languages assembler, C, and C++ are old, with many unsafe features and were not built to ease program verification.…”
Section: Eros/coyotosmentioning
confidence: 99%
“…Sridhar & Shapiro (2006) describe the language specification and a number of small innovations in its type system. The language is designed to be type safe and fast, and to allow reasoning about the low-level layout of data structures.…”
Section: Eros/coyotosmentioning
confidence: 99%
“…Due to the above interaction of polymorphism and unboxed mutability, a traditional HM-style inference algorithm cannot defer decisions about the mutability of types past their generalization. Therefore, current algorithms fix the mutability of types before generalization based on certain heuristics -thus sacrificing completeness [22]. In order to alleviate this problem, we use a new form of constrained types that range over both mutability and polymorphism.…”
Section: Type Inferencementioning
confidence: 99%
“…BitC is a more comprehensive approach, and by and large we have not found that direct support for representation provides any interesting difficulties in of itself. The difficulty lies in simultaneous support for representation, state, and polymorphism, which is the subject of Sridhar's paper in the current proceedings [23]. In email exchanges, Diatchki has reported that his enhancement to Haskell has had a significant impact on the implementation of their prototype operating system.…”
Section: Representationmentioning
confidence: 99%